Reproductive responses of rabbit does to a supplemental lighting program - Mattaraia, V G M; Bianospino, E.; Fernandes, S.; Vasconcelos, José Luiz Moraes [UNESP]; Moura, Ana Silvia Alves Meira Tavares [UNESP] (Elsevier B.V., 2005)
The objective was to investigate whether the productivity of rabbit does can be improved, when natural photoperiod is decreasing, by adopting a supplemental lighting program. Three experiments were conducted involving two groups: control, submitted to the natural decreasing photoperiod, and supplemented with a lighting program which provided 14 h light/24 h beginning at 10 weeks of age. In the first experiment, 20 nulliparous does, 10 from each group, were euthanized 8 h after being presented to a buck; the overall number of follicles, whose diameter exceeded I mm, was determined macroscopically. The right ovaries were collected, histologically analyzed, and electronically measured. In the second experiment, 30 nulliparous does, 15 from each group, were presented to a buck (day 1). Receptive does were euthanized on day 8 to evaluate embryonic survival (number of normal embryos/ovulation rate). In the third experiment, 48 nulliparous does, 24 from each group, were followed from the first presentation to the buck until the weaning of the first litter. The effect of treatment on reproductive and body weight traits of does, and litter performance traits, at birth and weaning, was evaluated. The average number of follicles whose diameter exceeded 1 mm was higher in the treatment group (12.05 +/- 1.07 vs. 8.63 +/- 1.00, P=0.03 7). Receptive does of the treatment group had heavier ovaries relative to those of the control group (790 +/- 59 vs. 470 +/- 64 mg, P=0.004), whereas no treatment difference regarding this trait was found for non-receptive ones. Treatment had a favorable effect on pregnancy rate of total exposed and of receptive does (80.0% vs. 33.3%, P=0.01, and 92.3% vs. 50.0%, P=0.02, respectively). The number of underdeveloped embryos was lower (0.067 +/- 0.380 vs. 2.500 +/- 0.455, P=0.004), embryonic survival up to day 8, and uterus weight was higher in the treatment group (0.839 +/- 0.075 vs. 0.534 +/- 0.087, P=0.033 and 13.83 +/- 0.72 vs. 10.99 +/- 0.84, P=0.037, respectively). Number of presentations tended to be lower (1.32 +/- 0.17 vs. 1.75 +/- 0.16, P=0.077) and adjusted litter size in the first reproductive cycle tended to be higher (7.09 +/- 0.89 vs. 5.22 +/- 0.68, P=0.091) in the treatment group relative to the control.
Keywords: embryonic survival; litter performance; ovarian follicle; ovulation rate; photoperiod; reproduction